PENGUATAN DAYA SAING DAERAH MELALUI KERJASAMA TERAS UTARA SULAWESI INDONESIA - Olilingo, Fahrudin Zain; Arsana, I Kadek Satria (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.04.TAHUN.2021DO - 10.24843/EEB.2021.v10.i04.p02, 2021)
ABSTRACT North-North Cooperation Agency is a form of inter-regional cooperation body consisting of 4 districts, namely North Gorontalo Regency, Bone Bolango Regency of Gorontalo Province, Buol Regency of Central Sulawesi Province, North Bolaang Mongondow Regency of North Sulawesi Province whose formation was facilitated by Gorontalo State University on September 17, 2014. The purpose of the establishment of north-north cooperation by Gorontalo State University is as the embodiment of the Tri Dharma of Higher Education and wants together with local governments from 4 districts to want this area to become a national strategic area bordering the country so as to form a new economic growth with the target of becoming a food and energy barn in eastern Indonesia. The achievement of these goals must be realized jointly by achieving togetherness for the common welfare. Strengthening the competitiveness of each region is very important to create the competitiveness of the north-north cooperation area that will be built with the commitment of the principle of mutual cooperation, mutual need and mutual strengthening. This paper will illustrate the factual condition of north-north cooperation that will be an important point in developing regional cooperation in the future.   Keywords : cooperation, strengthening, competitiveness, national strategic